Carbono incorporado en la construcción: estimación de emisiones asociadas a nuevas viviendas de interés social y prioritario en Bogotá, 2020-2030 (2020)
One of the sectors that has great responsibility in the generation of Greenhouse Gases (GHG) associated with Climate Change (CC) is the construction industry. Many of the studies that assess its environmental impacts have focused on the emissions associated with the operation of buildings. However, in recent decades, researchers have begun to study another fundamental aspect: the embodied carbon in buildings, which corresponds to the GHG emissions associated with its production. In Colombia, it is expected that during the next decade, numerous units of social housing (VIS and VIP) will be built in the region of Bogotá. The quantification of the embodied carbon in these dwellings is the main objective of this thesis. The study utilizes housing prototypes that seek to model the different building typologies and morphologies based on their height and construction system. The housing prototypes are based on seven case studies that are assessed using a simplified Life Cycle Analysis methodology. Among the main findings, it is highlighted that the embodied carbon in the prototypes varies between 158 and 231 kg CO2eq/m2 and that most of the emissions are concentrated during the product stage (81.6%), followed by the construction stage (9.6%), use stage (7.0%) and end of life stage (1.8%). On the other hand, the construction of VIS and VIP in Bogotá-Region during 2020-2030 is estimated between 27.4 and 28.8 million m2, projecting total emissions between 5.6 and 5.9 GtCO2eq.